Sustainable construction : green building design and delivery - Kibert, Charles J. (John Wiley & Sons, 2013)
Using the latest version of U.S. Green Building Council's Leadership in Energy and Environmental Design (LEED) rating system and other tools, Charles Kibert, in a clear and accessible writing style, addresses issues so that the reader can think critically and independently as part of the cutting edge in green building. New coverage includes of Carbon Neutral Design and Carbon Accounting. This book is a must for the builder/owner and manager looking to take advantage of the opportunities in this rapidly evolving field.